2016
DOI: 10.1002/jsfa.7867
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, chemical composition and biological activities ofSideritis raeseriBoiss. & Heldr.

Abstract: Sideritis species have been used in folk medicine for their antimicrobial, antiulcerogenic, digestive and anti-inflammatory properties. Over the years, the phytochemistry of the genus Sideritis has been studied, and various terpenoids, sterols, coumarins and especially flavonoid aglycones and glycosides have been identified. In particular, species from the Balkan Peninsula have been studied and were found to be rich in flavonoids, with valuable antioxidant activity. In the folk medicine of the Balkan countries… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…Menoikio had significant amounts of trans-pinocarveol, trans-verbenol and myrtenol that were shown to act as potent modifiers of GABA receptor function [42]. S. raeseri samples were also poor in monoterpenes but were rich in the sesquiterpenes trans-caryophyllene and its oxide, bicyclogermacrene and a-bisabolol; that is in agreement with previous studies [3]. Previous reports on S. raeseri and S. scardica identified bicyclogermacrene and spathulenol as the main constituents of the latter [34,36].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Menoikio had significant amounts of trans-pinocarveol, trans-verbenol and myrtenol that were shown to act as potent modifiers of GABA receptor function [42]. S. raeseri samples were also poor in monoterpenes but were rich in the sesquiterpenes trans-caryophyllene and its oxide, bicyclogermacrene and a-bisabolol; that is in agreement with previous studies [3]. Previous reports on S. raeseri and S. scardica identified bicyclogermacrene and spathulenol as the main constituents of the latter [34,36].…”
Section: Discussionsupporting
confidence: 91%
“…Elemental analysis was performed on the aerial parts, as the extractability of elements depends on the nature of the element and on the infusion conditions such as temperature and steeping time [30]. Among macrominerals (P, K, Ca, Mg), potassium was the most abundant among species as expected [21,36] and calcium [3]. Sodium was the most abundant in all plants while in the case of micro-minerals, in all species the order was Fe>Mn>Zn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvia, Mentha, and Sideritis are the main species belonging to Lamiaceae family. [8] The genus Sideritis, one of the most important members of the family Lamiaceae, involves more than 150 species widely distributed in Mediterranean area. This genus is represented by 46 species with >78.2% endemism rate in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…Sideritis subgenera comprises four sections; Hesiodia (Moench) Bentham, Empedoclia (Rafin) Bentham, Burgsdorffia (Moench) Briquet and Siderits L . Previous phytochemical studies on this genus have revealed the presence of a wide range of secondary metabolites, including terpenes, sterols, coumarins, flavonoids (aglycones and glucosides), phenylethanoid glucosides, phenolic acids and essential oils . Due to the excellent medicinal properties and commercial values, numerous pharmacological studies have been described and have mentioned a plethora of significant biological activities, such as anti‐inflammatory, antioxidant, antitumor, hepatoprotective, neuroprotective activity and effective against Alzheimer's disease …”
Section: Introductionmentioning
confidence: 99%